Transformasi Gaya Hidup Mahasiswa UINSU Tuntungan Analisis Kualitatif terhadap Pengaruh Media Sosial dan Tren Populer - Sayyid Musafa Alwan; Mulia Rahman; Muhammad Bagas; Afwan Syahril; Manurung Manurung (STIKes Ibnu Sina Ajibarang, 2025)
This study analyzes the influence of social media and popular trends on the lifestyle transformation of students at the State Islamic University of North Sumatra (UINSU) using a qualitative descriptive approach. This study aims to explore the understanding, experience, and meaning formed from the use of social media, especially TikTok and Instagram, in shaping students' lifestyles. Data were obtained through in-depth interviews with active UINSU students selected using purposive sampling techniques. The results of the study indicate that social media is the main medium in spreading lifestyle trends, including a minimalist lifestyle, which is often at odds with students' consumptive behavior.